TANGGUNG JAWAB BANK DALAM AKAD PEMBIAYAAN MURABAHAH ( STUDI PADA BANK MUAMALAT CABANG YOGYAKARTA ) - , YULIA AJENG PRATIWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to examine: (1) The legal relationship between the Bank and the customer in murabahah financing at Bank Muamalat Yogyakarta branch, (2) responsibility in financing murabahah Bank Muamalat branch in Yogyakarta. Research on Bank responsibility in murabahah financing at Bank Muamalat Branch Yogyakarta is a juridical empirical research, ie research conducted to obtain primary data with respect to the things that exist in the field by using a technique informant interviews. Data obtained both from the documents and the results of further research in the field of qualitative analysis and presented descriptively. The findings of the research: (1) that the legal relationship between the bank and its customers determines rights and obligations. Bank has implemented its obligations and get right to the good. (2) the Bank has fulfilled its responsibilities conferred by the presence of the power of financing the purchase of goods / power of attorney. Authorization for the purchase of goods / Wakalah was handed over to customers as extended arms of banks to choose their own items to be owned by the customer. All of the above are in accordance with the Law of the Republic of Indonesia Number 21 Year 2008 on Islamic Banking, Bank Indonesia Regulation Number: 7/6/PBI/2005 transparency of information regarding bank products and the use of customers' personal data, the National Fatwa Council of Ulama Islamic Council of Indonesia Number: 04/DSN-MUI/IV/2000 of Murabahah and Al Murabahah Agreement with Bank Muamalat Indonesia Yogyakarta Branch.